2004
DOI: 10.1016/j.cardiores.2004.07.001
|View full text |Cite
|
Sign up to set email alerts
|

in left human atrium: a potential contributor to atrial ectopy

Abstract: Our study revealed the presence of I(f) in left atrial myocytes and showed that I(f) parameters depend on atrial region. I(f) current densities were sufficient to convert the mathematical model of a quiescent human atrial cell into a "pacemaker cell". These data support the hypothesis of I(f) as a contributor to abnormal automaticity in human atrial tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 29 publications
0
27
0
1
Order By: Relevance
“…In contrast, the activation threshold of the I h of diseased cardiomyocytes is usually not shifted to more positive values compared with normal ventricular I h (76,139,177,182). Increased I h densities strongly raise the tendency of the ventricular muscle to develop ectopic, "pacemaker-like" action potentials and, thereby, contribute to arrhythmia and to sudden death (72,73,139,182,374,452).…”
Section: Cardiac Remodeling and Arrhythmiamentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast, the activation threshold of the I h of diseased cardiomyocytes is usually not shifted to more positive values compared with normal ventricular I h (76,139,177,182). Increased I h densities strongly raise the tendency of the ventricular muscle to develop ectopic, "pacemaker-like" action potentials and, thereby, contribute to arrhythmia and to sudden death (72,73,139,182,374,452).…”
Section: Cardiac Remodeling and Arrhythmiamentioning
confidence: 98%
“…Examination of mRNA levels in hypertrophied atrial and ventricular myocytes revealed an upregulation of HCN2 and HCN4 in different animal models (72,73,139,177,182,374,375,452). In addition, upregulation of HCN4 was found in human patients with end-stage heart failure (45).…”
Section: Cardiac Remodeling and Arrhythmiamentioning
confidence: 99%
“…Further studies into this association are necessary in order to reveal the role played by HCN channels in cases of AF electrical remodeling. Zorn-Pauly et al (12) found that increases in the I f current may cause atrial myocytes to function in a similar manner to pacemaker cells, subsequently increasing the local atrial automaticity, decreasing …”
Section: Discussionmentioning
confidence: 99%
“…All the dogs were implanted with pacemakers in a subcutaneous neck pocket using a previously described procedure (12,13). Following a 24-h recovery period, seven dogs were subjected to continuous right atrial pacing at 400 bpm for 50 days (AF group).…”
Section: Animal Model Establishmentmentioning
confidence: 99%
“…However, the exact role of HCN channels in generating and sustaining atrial arrhythmias is not known. Zorn-Pauly et al [20] found that increases in the If current may cause atrial myocytes to function like pacemaker cells, subsequently increasing the local atrial automaticity, decreasing the effective atrial refractory period and enhancing the risk of atrial arrhythmias. Zicha et al [21] analyzed atrial myocytes in dogs with rapid ventricular pacemaker activity and demonstrated that If enhancement, and the associated HCN channel overexpression, contributed to heart failure-induced ventricular arrhythmias.…”
Section: Pacemaker Funny Current In Healthy Heart and Under Pathologimentioning
confidence: 99%